COVID-19 and Face Masks – To Use or Not to Use! - Ramakrishnan, Devraj (Indian Journal of Community Health, 2020)
COVID-19 has evolved into a pandemic in quick time and being a droplet infection, it was quickly understood that prevention is the key. People started to use all types of masks and there was a panic as stocks started running out. Health care workers must use a triple layered surgical mask and those exposed to aerosol generating procedures must use an N 95 mask and these should be kept reserved for them, especially in a resource limited setting. Though initial advice from experts to the general public was not to use a mask in community settings unless they are sick or taking care of someone sick, the advice had to be later modified. Though CDC Atlanta currently advices everyone with no symptoms to wear cloth masks in the community, WHO opines there is no clear evidence to advise for or against mask use in the community. However, WHO encourages countries advising community mask use as it can generate useful evidence. Along with mask use, practicing all other preventive measures such as handwashing, cough etiquette, social distancing, quarantine and isolation are of utmost importance, without which, using surgical masks or even N95 masks, will not be much effective in the community setting.